The Effectiveness of Dual-Task Training on Upper Extremity Functions in Patients with Chronic Stroke: A Randomized Controlled Trial. - Tun, Su Sandi Hla; Wanpen, Sawitri; Nualnetr, Nomjit; Chatchawan, Uraiwan; Puntumetakul, Rungthip (NeuroRehabilitation, 2025)
Background: Patients with chronic stroke have difficulty in the simultaneous performance of upper extremity (UE) motor tasks while maintaining balance. The dual-task training (DTT) may help them improve their UE functions, trunk performance, and health-related quality of life. Objective: To compare the effects of DTT with dose equivalent conventional physical therapy (DECPT) on UE functions at baseline, week 2, and week 4 of the intervention in these patients. Methods: Twenty-eight patients with chronic stroke were randomly allocated into a dual-task training group (DTTG) (n = 14) and a dose equivalent control group (DECG) (n = 14). Both groups were trained for 1 h per session, 5 sessions per week for 4 weeks. Variables such as the Streamlined Wolf Motor Function Test for chronic stroke (SWMFT-C), Fugl-Meyer Assessment-Upper extremity (FMA-UE), Trunk Impairment Scale (TIS) and Stroke Impact Scale (SIS) were used to measure. Results: Statistically significant differences in the SWMFT-C functional ability scale and the TIS resulted in the group comparisons, however, no significant differences in other variables. Statistically, there was significant improvement in all post-training assessments when compared to pre-training in both groups. Conclusion: DTT can be used as an updated and effective therapeutic intervention for patients with chronic stroke to improve UE functions.